The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4103/0019-557x.200251
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity and overweight and their comparison by three growth standards among affluent school students aged 8–18 years in Rajkot

Abstract: Obesity and overweight emerged as an important public health problem in India. The present study was conducted to estimate the prevalence of obesity and overweight and compare it using three different standards among affluent school students aged 8-18 years from Rajkot, Gujarat. Anthropometric measurements of students of four schools from 3rd to 12th standards were taken. The prevalence of overweight and obesity was assessed using three standards - revised Indian Association of Pediatrics (IAP) 2015, WHO 2007,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous studies conducted in different cities of India have reported varying prevalence rates of overweight, ranging from 11.1% to 35.8%. (7,8) Our study findings are consistent with a retrospective cross-sectional study conducted in Tamil Nadu, which reported a 20% prevalence of overweight in children aged 5-18 years. ( 9)Other studies have reported lower prevalence rates, such as 15.6% in Uttarakhand and 11% in Hyderabad (10,11).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies conducted in different cities of India have reported varying prevalence rates of overweight, ranging from 11.1% to 35.8%. (7,8) Our study findings are consistent with a retrospective cross-sectional study conducted in Tamil Nadu, which reported a 20% prevalence of overweight in children aged 5-18 years. ( 9)Other studies have reported lower prevalence rates, such as 15.6% in Uttarakhand and 11% in Hyderabad (10,11).…”
Section: Discussionsupporting
confidence: 90%
“…The overall prevalence rate of obesity was 11.1%, and overweight was 15.3% as per the WHO 2007 standards. [10] The higher prevalence of overweight in the present study indicates that more children will become obese, while they become adult indicating rise in number of obesity in coming decades. The present study findings indicate that in the overweight category, girls were overweight (52.5%) when compared to the boys (47.5%) and in the obese category, boys were (51.5%) and girls were (48.4%).…”
Section: Discussionmentioning
confidence: 50%
“…(Table 4) that 15.3% were overweight and 11% were obese by WHO standards. 5 A cross sectional study was conducted in six zones of Ahmedabad Municipal Corporation among children aged 10-19 years. Brambhatt KR et al in this study observed that 13.3% adolescents were overweight and 5.4% were obese.…”
Section: Resultsmentioning
confidence: 99%